2014
DOI: 10.5751/es-06474-190236
|View full text |Cite
|
Sign up to set email alerts
|

Communicating adaptation with emotions: the role of intense experiences in raising concern about extreme weather.

Abstract: ABSTRACT. Adaptation to extreme weather is often considered as having a low urgency and being a low priority governance option, even though the intensity of extreme weather events is expected to increase as a result of climate change. An important issue is how to raise an adequate level of concern among individuals, policy makers, and broader decision makers in companies and organizations so that adaptation to extreme events becomes mainstream practice. We conducted 40 indepth interviews with individuals from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…These various lines of research have come together in, and inevitably brought greater attention to, the role of emotions in climate change communication. This greater focus on the affective and emotional (as opposed to just the cognitive) side of climate change is partly driven by the irrational‐seeming lack of concern about the problem and persistent psychological distancing, partly by the often intense emotional reactance to climate change (and its messengers) by those who do not ‘believe’ in climate change, and partly by the increasingly observed sense of despair and hopelessness among those who understand the science and experience early impacts and/or the lack of commensurate action . Some researchers emphasize that emotions play a critical role in decision‐making, while others recognize their importance in issue acceptance, motivation or resistance to action and policy‐support or opposition, and in health and well‐being .…”
Section: The Fieldmentioning
confidence: 99%
“…These various lines of research have come together in, and inevitably brought greater attention to, the role of emotions in climate change communication. This greater focus on the affective and emotional (as opposed to just the cognitive) side of climate change is partly driven by the irrational‐seeming lack of concern about the problem and persistent psychological distancing, partly by the often intense emotional reactance to climate change (and its messengers) by those who do not ‘believe’ in climate change, and partly by the increasingly observed sense of despair and hopelessness among those who understand the science and experience early impacts and/or the lack of commensurate action . Some researchers emphasize that emotions play a critical role in decision‐making, while others recognize their importance in issue acceptance, motivation or resistance to action and policy‐support or opposition, and in health and well‐being .…”
Section: The Fieldmentioning
confidence: 99%
“…In sum, their analysis can largely be seen as an exploration of changes in professional framings around climate change adaptation. Vasileiadou and Botzen (2014), however, suggest that when focusing on extreme weather one should distinguish between framings by experts and those by lay persons. The key difference between these groups is the level of awareness of climate change, which is much higher in the expert community than among lay people.…”
Section: Findings Findings On Problems Choicesmentioning
confidence: 99%
“…Vasileiadou and Botzen (2014) suggest that bridging different problem framings is very difficult because expert assessments of climate risks are derived from models, whereas risk assessments by lay people are more determined by direct experience. Secondary information, i.e., hearing about the risks of extreme weather, is far less effective in enhancing awareness.…”
Section: Findings Findings On Problems Choicesmentioning
confidence: 99%
“…Water reuse therefore grants flexibility in the alleviation of water Within this body of work, there is also a link with policy implementation and behavior-for example, Hine et al [28] shows how messages with strong negative emotions increase intention. In ecological management, Vasileiadou and Botzen [29] have found that it is not merely experience that moves individuals to actions, but the emotions attached to such experiences and the intensity of the felt emotions-the more intense the emotions felt, the more likely the policy population will be moved to action, that is "individuals who have experienced an intense, life-threatening event have a significantly higher level of concern than those without such an experience".…”
Section: Introductionmentioning
confidence: 99%